Synergy in Accelerating the Reduction of Stunting in Seram Bagian Timur Regency, Maluku Province - Askiah Takaba; Azhar Azhar; Katriza Imania (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyse the synergy in accelerating the reduction of stunting in Seram Bagian Timur Regency and to identify the factors that support and hinder the acceleration of stunting reduction in Seram Bagian Timur Regency. This study uses a qualitative approach. Data collection techniques were conducted through interviews, observations, and document studies. This study uses the concept of synergy which includes two main dimensions: communication and coordination. The results of the study indicate that synergy in accelerating the reduction of stunting in Seram Bagian Timur Regency has shown progress through the active role of the local government in communication, cross-sectoral coordination, and the implementation of specific and sensitive interventions. However, the synergy achieved is not yet optimal. In terms of communication, there are still limitations in communication media such as pocketbooks and leaflets, which hinder information dissemination, and two-way communication or feedback has not been effective, as evidenced by the presence of audiences providing irrelevant responses. In terms of coordination, weaknesses lie in the low capacity of some cadres and the lack of awareness among village governments and communities regarding the urgency of stunting. Budget constraints and shortages of health workers such as midwives, nurses, and nutrition educators limit the scope of services, particularly in remote areas. Difficult geographical conditions further complicate efforts to accelerate stunting reduction. Therefore, it is recommended to enhance synergy in accelerating stunting reduction in Seram Bagian Timur District through: strengthening human resources, including improving cadre capacity and equitable distribution of health workers; increasing awareness among village governments and communities about the urgency of stunting; strengthening programme funding; and implementing interventions tailored to the geographical conditions of the area. Keywords: Synergy; Stunting; Communication; Coordination;